Associations of white matter hyperintensities with networks of gray matter blood flow and volume in midlife adults: A coronary artery risk development in young adults magnetic resonance imaging substudy. Issue 12 (15th April 2022) - Kim, William S. H.; Luciw, Nicholas J.; Atwi, Sarah; Shirzadi, Zahra; Dolui, Sudipto; Detre, John A.; Nasrallah, Ilya M.; Swardfager, Walter; Bryan, Robert Nick; Launer, Lenore J.; MacIntosh, Bradley J.
Abstract: White matter hyperintensities (WMHs) are emblematic of cerebral small vessel disease, yet effects on the brain have not been well characterized at midlife. Here, we investigated whether WMH volume is associated with brain network alterations in midlife adults. Two hundred and fifty‐four participants from the Coronary Artery Risk Development in Young Adults study were selected and stratified by WMH burden into Lo‐WMH (mean age = 50 ± 3.5 years) and Hi‐WMH (mean age = 51 ± 3.7 years) groups of equal size. We constructed group‐level covariance networks based on cerebral blood flow (CBF) and gray matter volume (GMV) maps across 74 gray matter regions. Through consensus clustering, we found that both CBF and GMV covariance networks partitioned into modules that were largely consistent between groups. Next, CBF and GMV covariance network topologies were compared between Lo‐ and Hi‐WMH groups at global (clustering coefficient, characteristic path length, global efficiency) and regional (degree, betweenness centrality, local efficiency) levels. At the global level, there were no between‐group differences in either CBF or GMV covariance networks. In contrast, we found between‐group differences in the regional degree, betweenness centrality, and local efficiency of several brain regions in both CBF and GMV covariance networks. Overall, CBF and GMV covariance analyses provide evidence that WMH‐related network alterations are present at midlife. Abstract : In this study, we stratified a sample of midlife adults by white matter hyperintensities (WMH) burden into two groups (Lo‐WMH and Hi‐WMH). We then generated group‐level covariance networks of cerebral blood flow (CBF) and gray matter volume (GMV) through pairwise correlations across participants. We show that CBF and GMV covariance networks exhibit small‐world topologies and can be organized into modules that are consistent between groups. We also report regional, but not global, network alterations within CBF and GMV covariance networks in the Hi‐WMH group.